Change in children's physical activity and sedentary time between Year 1 and Year 4 of primary school in the B-PROACT1V cohort - Russell Jago; Emma Solomon-Moore; Corrie Macdonald-Wallis; Simon J. Sebire; Janice L. Thompson; Deborah A. Lawlor (BMC, 2017)
Abstract Background The aim of this study was to examine how children's and parents' physical activity changes from Year 1 (5-6) to Year 4 (8-9 years of age). Methods Data are from the Bristol (UK) B-PROACT1V cohort. Fifty-seven primary schools were recruited when the children were in Year 1, with 1299 children and their parents providing data. Forty-seven schools were re-recruited in Year 4, with 1223 children and parents providing data (685 of whom participated in Year 1). Children and at least one parent wore an accelerometer for 5 days including a weekend and mean minutes of sedentary time, moderate-to-vigorous intensity physical activity (MVPA) and accelerometer counts per minute (CPM) were derived. Multiple imputation was used to impute missing data for all 1837 families who took part, including those who participated at just one time. Paired t-tests examined if there was statistical evidence of change in accelerometer measures. Results Multiple imputation and observed data were comparable and results using complete observed data were mostly the same as those using imputed data. Imputed data showed that mean boys' CPM decreased from 747 to 673 (difference in mean 74 [95% CI 45 to 103]) and girls' from 686 to 587 (99 [79 to 119]). Boys' time spent in MVPA reduced from 72 to 69 (3 [0 to 6]) and girls' from 62 to 56 (7 [4 to 9]) minutes per day. There were increases in sedentary time for both boys (354 to 428 min, 74 [61 to 88]) and girls (365 to 448, 83 [71 to 96]). There was no evidence of change in parent CPM or MVPA. Mothers' sedentary time increased by 26 min per day [16 to 35]. Conclusions There were similar increases in sedentary time in girls and boys between age 5-6 and 8-9, and decreases in MVPA that were more marked in girls. The similarity of multiple-imputed and complete observed data suggest that these findings may not be markedly affected by selection bias. Result support early interventions to prevent the age-related decline in children's physical activity.